1997
DOI: 10.1055/s-0038-1655730
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Novel Mutations in Hereditary Protein S Deficiency

Abstract: SummaryWe report the application of single-stranded conformation polymorphism (SSCP) analysis to the screening of 15 functionally important Protein S (PS) gene (PSα) regions (4.243 Kb) in 6 unrelated families with PS deficiencies. Direct sequencing of the fragments with altered migration patterns led to the identification of the corresponding molecular alterations. A missense mutation, G to T transversion at codon Cys598, and two different alterations, leading either to allelic exclusion, or premature terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Nevertheless, screening for PROS1 gene mutations has been performed in a number of studies. The proportion of cases where no mutations are detected varies widely between studies [10,17,[23][24][25][26][27][28][29][30][31][32][33]. When all cases are pooled together, PROS1 gene mutations are not detected in 47% of PS deficient families.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, screening for PROS1 gene mutations has been performed in a number of studies. The proportion of cases where no mutations are detected varies widely between studies [10,17,[23][24][25][26][27][28][29][30][31][32][33]. When all cases are pooled together, PROS1 gene mutations are not detected in 47% of PS deficient families.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now many PROS1 mutations have been found associated with the PS-deficient phenotype [Gandrille et al, 1997]. Most of these mutations have been identified in the type I and in the few type II PS-deficient pedigrees, as well as in several pedigrees with coexistence of both type I and III phenotypes [Andersen et al, 1996;Beauchamp et al, 1996;Borgel et al, 1996;Bustorff et al, 1997;Simmonds et al, 1997;Espinosa-Parrilla et al, 1999]. By contrast, no PROS1 mutations clearly associated with the deficient phenotype are identified in most of the pedigrees presenting only the type III phenotype [Borgel, et al, 1996;Espinosa-Parrilla et al, 1997;Espinosa-Parrilla et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, about 100 different mutations, most of them point mutations or short deletions or insertions, have been identified in the PROS1 gene of more than 135 PS-deficient proposita [Gandrille et al, 1997]. Most of the mutations have been reported to be associated with type I PS deficiency, some of which have been shown to cosegregate with both type I and III PS phenotypes coexisting in the same family [Anderson et al, 1996;Beauchamp et al, 1996;Bustorff et al, 1997;Li and Long, 1997;Mustafa et al, 1997a;Simmonds et al, 1997]. By contrast, although type III PS deficiency may be found at a similar or even higher prevalence than type I PS deficiency [Mateo et al, 1997], in a recent study no PROS1 mutation was found in more than 50% of the type III probands [Borgel et al, 1996].…”
Section: Introductionmentioning
confidence: 99%